Shear capacity of masonry walls externally strengthened using Flax-TRM composite systems: experimental tests and comparative assessment. (20th November 2020) - Ferrara, Giuseppe; Caggegi, Carmelo; Martinelli, Enzo; Gabor, Aron
Highlights: Flax textiles are an efficient reinforcement in lime-based composites. Flax TRMs enhance the shear capacity of masonry walls. Flax TRM reinforcement guarantees a post-failure integrity of the wall. Abstract: A growing environmental awareness is gradually changing the entire economic system and consequently, the building materials sector is increasingly interested in innovative sustainable solutions. The use of plant fibres as reinforcement in inorganic composite systems, generally referred to as Textile Reinforced Mortar (TRM), represents an innovative alternative to the use of more traditional high-strength inorganic fibres, which reduces the environmental impact of the composite. However, there are several unsolved issues regarding the correct mechanical behaviour of such innovative systems. Various studies have been conducted to assess the fibre-to-mortar bond properties and to investigate the tensile behaviour of TRMs based on plant textiles, such as flax, hemp, coir, sisal, and jute. Moreover, there is still a lack of experimental evidence concerning the efficiency of the composite material once applied to structural elements. Therefore, this paper reports on an experimental study on the shear capacity of walls strengthened by two TRMs characterised by a different amount of textile reinforcement. The experimental results are discussed and compared with the results of theoretical models derived from formulations proposed by the standards in this field. This study shows that Flax-TRM reinforcement enhances the strength and ductility of a masonry assemblage, confirming the potential utility of such materials. Furthermore, it points out some limitations of this reinforcement technique and paves the way for future studies aimed at improving the efficiency of the entire system.